Does a value-added smile curve imply an environmental frown curve? - Schwarzbauer, Wolfgang,Bittó, Virág,Koch, Philipp,Steininger, Jonathan (EcoAustria - Institute for Economic Research, 2024)
Global value chains (GVCs) play a crucial role in today's international trade. High value-added activities tend to cluster at the start and the end of GVCs, resulting in a U-shaped relationship across production steps known as the
10419/306347
Keywords: Graue Literatur; Greenhouse gas emissions; Sustainable Development; Transition towards green economy; Global Value Chains; Multi-Regional Input-Output Model; International Trade; Climate change